Nuclear Localization Signal and p53 Binding Site in MAP/ERK Kinase Kinase 1 (MEKK1). Issue 12 (8th October 2015) - Chipps, Elizabeth; Protzman, April; Muhi, M. Zubayed; Ando, Shoko; Calvet, James P.; Islam, M. Rafiq
ABSTRACT Previously, we showed that Mekk1 translocates to the nucleus, interacts with tumor suppressor protein p53, and co‐represses PKD1 transcription via an atypical p53 binding site on the minimal PKD1 promoter (JBC 285:38, 818–38, 831, 2010). In this study, we report the mechanisms of Mekk1 nuclear transport and p53 binding. Using GFP‐linked constitutively active‐Mekk1 (CA‐Mekk1) and a deletion strategy, we identified a nuclear localization signal (HRDVK) located at amino acid (aa) residues 1, 349–1, 353 in the C‐terminal Mekk1 catalytic domain. Deletion of this sequence in CA‐Mekk1 and full‐length Mekk1 significantly reduced their nuclear translocation in both HEK293T and COS‐1 cells. Using co‐immunoprecipitation, we identified an adjacent sequence (GANLID, aa 1, 354–1, 360) in Mekk1 responsible for p53 binding. Deletion of this sequence markedly reduced the interaction of Mekk1 with p53. Mekk1 does not appear to affect phosphorylation of Ser15, located in the Mdm2 interaction site, or other Ser residues in p53. However, Mekk1 mediates p53 protein stability in the presence of Mdm2 and reduces p53 ubiquitination, suggesting an interference with Mdm2‐mediated degradation of p53 by the ubiquitin‐proteasome pathway. J. Cell. Biochem. 116: 2903–2914, 2015. © 2015 Wiley Periodicals, Inc.